Pemanfaatan Edoo Sebagai Bentuk Inovasi Layanan Di Perpustakaan Sman 15 Bandung - Mellinia, Annisa; Hadiapurwa, Angga (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
The purpose of this study is to utilize the Edoo digital library application at SMAN 15 Bandung as a form of service innovation in the library. Data collection techniques were carried out by observation with observations and interviews accompanied by literature study. Results from this study shows that the Edoo digital library application useful in assisting learning activities, the advantages and disadvantages of the Edoo digital library application are a challenge for the SMAN 15 Bandung library